"ANTIBIOTIC RESISTANCE IN KARACHI, PAKISTAN: LINEZOLID'S ROLE IN STEMMING THE TIDE" - Syed Akif Uddin; Lubna Bashir; Syeda Tayyaba Asif; Madiha Jamsed; Maria Khan; Humera Naz; Mahwish Mahmood Siddiqui (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Aims: In order to determine the main causes of the development of conventional antibiotic resistance in the area, this survey-based study sought to assess the prevalence of antibiotic resistance among common infections in Karachi, Pakistan. The study also emphasizes Linezolid's part in fighting resistant infections.Methodology: Using a cross-sectional survey approach, the study gathered information from 500 individuals receiving antibiotic therapy for illnesses around Karachi. Structured questionnaires including demographics, clinical history, and antibiotic use were used to collect data. Bacterial species and their resistance to common antibiotics, such as ciprofloxacin, amoxicillin, cephalosporins, Linezolid and tetracycline, were determined through laboratory testing. Antibiotic resistance and demographic characteristics were correlated using statistical analysis. The significance of Linezolid in treating resistant infections was also assessed. The data was analyzed using descriptive statistics.Results: The findings showed that antibiotic resistance was quite prevalent in Karachi, with amoxicillin, ciprofloxacin, and cephalexin showing the strongest resistance. With more than 70% of isolates demonstrating resistance to first-line antibiotics, Escherichia coli and Klebsiella pneumoniae were the most often isolated pathogens. Antibiotic abuse and misuse, self-medication, incomplete antibiotic regimens, and inadequate infection control procedures in healthcare settings were all factors that contributed to antibiotic resistance. The effectiveness of Linezolid in treating Gram-positive bacteria that are resistant to numerous medications demonstrated the drug's importance in treating resistant infections.Conclusion: In order to stop the spread of antibiotic resistance, the study shows a worrying increase in antibiotic resistance in Karachi, Pakistan. This highlights the urgent need for better antibiotic stewardship, awareness campaigns, and more robust regulatory measures. The results highlight how critical it is to address the underlying causes of antibiotic resistance through public health initiatives. With the introduction of Linezolid, there is a hope for treating resistant infections, especially those brought on by Gram-positive bacteria that are resistant to numerous medications.